Overseas links as export conduits - Aoife Hanley (Kiel Institute for the World Economy (IfW), 2009)
This paper investigates the relationship between exports and overseas links using data from the UK Community Innovation Survey. Overseas vertical and horizontal links are associated with an average increase in export intensity of 74 and 156 percent for vertical and horizontal overseas links respectively. Firm size shows no significant interactions with overseas links. The data suggests that overseas links are a relatively infrequent form of conducting trade. My findings support the role of Government in fostering overseas links despite their rarity, since they are effective export conduits.
Keywords: F14; F23; L24; L14; 330; Exports; networks; outsourcing; vertical integration; Multinationales Unternehmen; Auslandsniederlassung; Outsourcing; Vertikale Konzentration; Export; Exportindustrie; Großbritannien